Effect of Garlic (Allium sativum) Supplementation on the Growth Performance of Crossbred Calves - Balamurugan, N; Sundaram, SM; Sivakumar, T; Rajkumar, JSI (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. Trial was conducted to assess the effects of different garlic supplementation methods on the performance of crossbred calves. Jersey crossbred calves of both sexes were randomly separated into three treatments (T1, T2 and T3) of six calves in each group.Â Calves in T1 group were supplemented with garlic powder at the dose rate of 250 mg/kg BW in water whereas calves in the T2 group were supplemented with 250 mg/kg BW in concentrate feed and the T3 group was treated as control. The data on growth rate in terms of body weight, average daily gain, feed intake, faecal consistency score, faecal egg count and disease incidence were analysed as per standard procedures. It was found that the calves in T1 and T2 group gained significantly higher overall body weight and average daily gain compared with calves in T3 group. No significant difference was observed in feed intake and feed conversion efficiency between the treatment groups. The faecal consistency score and faecal egg count remained the same in all the treatment groups.Key words: crossbred calves, Jersey, garlic supplementation, growth parametersAbstrak. Percobaan dilakukan untuk meneliti pengaruh metode suplementasi bawang putih terhadap performa sapi peranakan silang. Sapi peranakan silang Jersey jantan dan betina dibagi secara acak ke dalam tiga perlakuan (T1, T2 dan T3) masing-masing 6 ekor. Sapi T1 diberi 250 mg/kg bobot bawang putih bubuk di air, T2 diberi 250 mg/kg bobot bawang putih bubuk di pakan konsentrat, dan T3 adalah kontrol. Data tingkat pertumbuhan, penambahan bobot harian, jumlah konsumsi, nilai konsistensi feces, jumlah telur cacing dan kejadian penyakit dianalisis sesuai standar prosedur. Ditemukan bahwa sapi kelompok T1 dan T2 memiliki total kenaikan bobot dan penambahan bobot harian yang lebih tinggi dibanding sapi kelompok T3. Tidak ada perbedaan nyata yang ditemukan pada jumlah konsumsi dan efisiensi konversi pakan antara kelompok perlakuan. Nilai konsistensi feces dan jumlah telur cacing tetap sama di semua kelompok perlakuan.Kata kunci: sapi perankaan silang, Jersey, suplementasi bawang putih, parameter pertumbuhan